Implementation of enterprise resource planning for improving enterprise value chain - Chew, Jian You. (2009)
As more and more organizations move from functional to process-based IT infrastructure, ERP systems are becoming one of today’s most widespread IT solutions. Nowadays, ERP system is not exclusive for giant organizations, but an emerging trend for the SMEs to adopt ERP system to improve their competitiveness in the global market. However, ever since the emergence of ERP concept, ERP implementation project is notorious for its high failure rate. ERP implementation should not be mistaken as just simple installation of IT infrastructure; it involves organizational changes, business process re-engineering and even a paradigm shift for the management. Studies on past examples revealed that the uncertainties and evolving environment in an ERP project had been the main culprits of failures. This project studies an effective decision support framework for adopting an ERP system, introducing active management in dealing with uncertainties to minimize risk of failure. An implementation lifecycle is proposed, providing details of decision making processes throughout the implementation. Relevant theories and models such as Theory of Constraint, Real Option Theory and ex-ante cost based analysis are proposed and integrated into the implementation lifecycle. Real Option Theory (Fuzzy payoff valuation) will be used in modeling the ERP project investment. Application of Theory of Constraint in business process re-engineering will be explored. Majority of the previous studies are made on huge and well established organization, less effort had been put on SMEs. Lacking of both financial resources and expertise from various business functions, it is difficult for the SMEs to make well-informed and reliable decisions throughout the ERP implementation. The proposed methodologies in this project are orientated from the perspective of SME. To validate the proposed methodology, a case study was done on a SME, Charterway Co Ltd., a logistics and trading company. The company started the adoption of a self-developed ERP system in year 2004, and the system went into routine use in late 2005. The case study looked deeply into the implementation process, using the proposed methodologies with the relevant theories application.